Liquid Inclusion Collision and Agglomeration in Calcium-Treated Aluminum-Killed Steel - Ferreira, Mauro E.; Pistorius, Petrus Christiaan; Fruehan, Richard J. (Frontiers in Materials, 2021)
This work addresses conflicting results in the literature regarding liquid inclusion agglomeration. To assess whether liquid calcium aluminates do agglomerate in liquid steel, laboratory experiments were performed: melting electrolytic iron, deoxidizing the melt with aluminum and subsequently calcium treating the deoxidation products (alumina and magnesia-alumina spinel inclusions). Under laboratory conditions, solid spinels and alumina inclusions were successfully modified, producing a new population of much smaller calcium aluminate inclusions. The new population of inclusions forms because the presence of calcium in the liquid steel destabilizes alumina and MgO-alumina inclusions, which then dissolve into the melt. These liquid inclusions exhibited a weak but statistically significant tendency to agglomerate. Laboratory results were assessed in the light of different collision mechanisms. Agglomeration mainly occurs by Stokes and laminar fluid flow collision when no external stirring is imposed. Monte Carlo simulations of collisions agree reasonably well with experimental results. For industrial conditions, where the liquid steel is agitated by argon bubbling and/or electromagnetic stirring, turbulent collisions dominate.